التحري عن المستوى الجرثومي وعلاقتة بمستوى الكاربون العضوي - A. redha, yahia (University of Thi-Qar Journal of Science, 2011)
The study was carry out for detection the microbial contamination in waters and sedimentsof Abu-Zariq Marsh at Al-Nassiriyah city southeren of Iraq. From March 2009 to Auguest 2010three stations have been were taken bacterial account such as: Total coliform (Tc), Fecalcolifirm (Fc), Fecal enterococci (Fe), and their relationship with the presence of pathogenicbacteria (Salmonella). Also in order determe the total organic carbon in sediments (TOC%) andits relationship with microbial indicators. The resultes appeared high of level of contaminationin second station during Winter and Autum and lowest level in thired station. Total coliformranged between 1700 and 5400 cell/100ml, Fecal coliform ranged between 1500 and 4500cell/100ml , Fecal enterococci ranged between 4000 and 15000cell/100 ml. and Salmonella spp.were isolated from 7 (58.3%) out of 12 water samples and 100% from sediments ,Total organiccarbon in sediment was 1.9% in the second station during Spring,whereas the lowest range was0.72% in the first station during Autum, whith presence of positive correlation with numbers ofbacteria.